ANALYSIS OF LIBRARY SATISFACTION SURVEY - Annisa Rahmadanita; Hasmiati Hasmiati; Umanah Umanah (Indonesian Journal of Librarianship, 2020)
Problem Statement: The author focuses on the problem of decreasing the number of Library Department of IPDN visitors in 2018. Purpose: This study is focused on answering how the satisfaction of IPDN library users. Method: The author collected data through a questionnaire distributed to 51 respondents in the Praja category. Results: The results showed that the dimensions of collection types, completeness of collections, book search on the shelves, time of visit and borrowing time for library collections needed improvement, while in the dimensions of collection search tools, easiness of library users to obtain information, attitude and behavior of librarians needed improvement. Conclusion: Library users were satisfied with the implementation of the library, especially in the dimensions of the attitude and behavior of librarians, search tools collection and ease of information search. The author suggests that IPDN Libraries need to survey the needs of the type of library collections that are needed by users, update written regulations relating to library service hours, increase lending time for library collections that can be borrowed and brought home, and set shelving schedules on a regular and regular basis.